Cinema, história pública e educação: circularidade do conhecimento histórico em Xica da Silva (1976) e Chico Rei (1985) - Rodrigo de Almeida Ferreira (2014)
The dissertation Cinema, public history and education: circularity of historical knowledge in Xica da Silva (1976) and Chico Rei (1985) investigates the historical movie genre from the viewpoint of mediation, divulgation and production of historical knowledge in both school and non-school spaces. This analysis of historical movies was based on the social imaginaries in the movies built at the interface between historiography and other narrative fields such as literature, music and carnival. It points to the dimensions of public history as a means of production and divulgation of historical knowledge in dialogue with other not necessarily academic areas. These reflections were based on the analysis of the movies Xica da Silva (directed by Cacá Diegues, 1976) and Chico Rei (directed by Walter Lima Júnior, 1985). In the social imaginary, the paths of the former slaves, the main characters, are emblematic in the history of Minas Gerais and have been presented in various narrative supports. These characters afford an opportunity for the movies to deal with social historical aspects of the Portuguese America Period, mainly in Minas Gerais during the 18th century. Historical movies also allow observing the temporal context of their production and divulgation. Both of these movies were made during the Brazilian civil-military dictatorship and dealt with this period through allegories, metaphors, suggestions and/or jokes. This study is transdisciplinary in nature, delving into the areas of education, history and cinema. The analysis of the relationship between academic production and education beyond the school space through the movies was structured as follows: 1) the construction of the movie narratives in a dialogue with the forms of historical representation as a means of expression of public history, 2) the role of historical movies and their narrative characteristics in relation to the State educational and cultural policies with emphasis on the relationship between these movie projects and Embrafilme, the Brazilian State movies agency, 3) the analysis of Xica da Silva (1976) and Chico Rei (1976) with emphasis on the appropriation, circularity and resignification of social imaginaries of Brazilian history that run through the past-present timeline, and 4) the educational impact of these movies as covered by the press and their introduction to school spaces through didactic books and teacher training. This approach of historical movies and education reveals methodological possibilities within public history.